Simultaneous Determination of Chromium Species in Water and Plant Samples at Trace Levels by Ion Chromatography-Inductively Coupled Plasma-Mass Spectrometry - Sel, Sabriye; Erulas, Fatih Ahmet; Turak, Fatma; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2019)
Ion chromatography-inductively coupled plasma-mass spectrometry (IC-ICP-MS) was used for the identification and quantification of chromium species. Chromium(III) and chromium(VI) were separated and determined by IC-ICP-MS. The separation was achieved using an anion exchange column with 0.55 M HNO3 as mobile phase. It was a particular goal of this work to exclusively use nitric acid for elution in order to reduce interferences in the ICP-MS system. Analytical figures of merit were calculated under the optimum conditions by developing calibration plots in a concentration range of 0.50-250 mu g/L for both species. The detection limits for Cr(III) and Cr(VI) were 0.09 and 0.03 mu g/L, respectively. Spiked recovery tests were used to evaluate the applicability of the analytical method in environmental samples, and the recoveries ranged between 97 and 103% for both analytes. The accuracy of the method for total chromium content was validated through the analysis of a spring water-certified reference material (UME 1201), and the obtained results were in good agreement with the certified value. Lettuce seedlings were cultivated to evaluate the intake levels of these species. In addition, the bioaccessibility of Cr(III) and Cr(VI) from the lettuce seedlings in simulated gastric and intestinal fluids media was examined.
Keywords: Cr(III); Cr(VI); ion chromatography-inductively coupled plasma-mass spectrometry; lettuce seedlings; speciation; PERFORMANCE LIQUID-CHROMATOGRAPHY; HPLC-ICP-MS; Chemistry